2021
DOI: 10.1002/hlca.202000222
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐Induced Perovskite‐to‐non‐Perovskite Phase Transition in CsPbBr3

Abstract: The expanding range of optoelectronic applications of lead‐halide perovskites requires their production in diverse forms (single crystals, thin‐ and thick‐films or even nanocrystals), motivating the development of diverse materials processing and deposition routes that are specifically suited for these structurally soft, low‐melting semiconductors. Pressure‐assisted deposition of compact pellets or thick‐films are gaining popularity, necessitating studies on the pressure effects on the atomic structure and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…The diffraction peaks at 15.3°, 21.7°, and 31.0° for the Er/Yb:CsPb(Cl/Br) 3 flake correspond to the (100), (110), and (200) planes of the cubic structure perovskite, [ 27,28 ] α‐CsPb(Cl/Br) 3 , while diffraction peaks with relatively weak intensity at 12.7°, 20.3°, and 28.7° correspond to the (012), (022), and (122) planes of orthorhombic structure perovskite, δ‐CsPb(Cl/Br) 3. [ 27,29 ] This implies that the Er/Yb:CsPb(Cl/Br) 3 flake are mixture phase materials, in which the α‐phase is the dominant phase and the δ‐phase occupies a small amount. As compared to the CsPb(Cl/Br) 3 samples without Ln‐doping, the diffraction peaks of the Ln‐doped flakes increased by ≈0.1°, indicating that the Ln‐doping causes the lattice contraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diffraction peaks at 15.3°, 21.7°, and 31.0° for the Er/Yb:CsPb(Cl/Br) 3 flake correspond to the (100), (110), and (200) planes of the cubic structure perovskite, [ 27,28 ] α‐CsPb(Cl/Br) 3 , while diffraction peaks with relatively weak intensity at 12.7°, 20.3°, and 28.7° correspond to the (012), (022), and (122) planes of orthorhombic structure perovskite, δ‐CsPb(Cl/Br) 3. [ 27,29 ] This implies that the Er/Yb:CsPb(Cl/Br) 3 flake are mixture phase materials, in which the α‐phase is the dominant phase and the δ‐phase occupies a small amount. As compared to the CsPb(Cl/Br) 3 samples without Ln‐doping, the diffraction peaks of the Ln‐doped flakes increased by ≈0.1°, indicating that the Ln‐doping causes the lattice contraction.…”
Section: Resultsmentioning
confidence: 99%
“…[ 27 ] They are actually nonperovskite semiconductors with indirect bandgap. [ 27,29 ] The valence band comprises contributions from s‐orbital of Pb atoms (s‐Pb) and the p‐orbital of Br atoms (p‐Br), while the conduction band comprises contributions from p‐orbital of Pb atoms (p‐Pb) and p‐orbital of Br atoms (p‐Br). [ 27 ] The photoinduced halide ions migration will also cause a drift of its conduction band and valence band.…”
Section: Resultsmentioning
confidence: 99%
“…In the last few decades, increasing numbers of research on MHPs under high pressure have been reported, adding numerous new structures with novel physical properties to the family of perovskite materials. In inorganic MHPs, for instance, CsPbI 3 and CsPbBr 3 have been reported to undergo the conversion from the Pm m perovskite structure with corner-shared BX 6 octahedra to the Pnma structure with double chains of edge-shared PbX 6 under pressure; , 2D CsPb 2 X 5 (X = Br and I) with face-shared BX 6 octahedra (space group I 4/ mcm ) was synthesized by the direct phase separation of 1D CsPbI 3 with edge-shared PbX 6 octahedra (space group C 2/ m ) at high-pressure and temperature ( P – T ) conditions . The tunable connectivity modes of BX 6 octahedra observed in inorganic MHPs under high P – T conditions provide a new possibility for the design and synthesis of more perovskite-related structures, but the underlying mechanisms remain unclear in organic MHPs due to the limitation of the pressure-induced amorphization and temperature-induced decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Metal halide perovskites (MHPs) have been attracting increasing attention in the field of optoelectronic applications because of their low cost and excellent optoelectronic properties. The record power conversion efficiency (PCE) of single-junction perovskite solar cells (PSCs) based on CH 3 NH 3 PbI 3 now exceeds 25% . However, the toxicity of lead-containing perovskites hinders their large-scale commercialization.…”
mentioning
confidence: 99%
“…In order to suppress the nonradiative energy loss, formation of DY centers should be minimized. Transient absorption spectroscopy was used to probe charge transport in Cs 2 AgBiBr 6 thin films, revealing a significant density of traps, proposed to be associated with Br vacancies in the lattice . First-principles calculations were carried out to elucidate formation and charge transition levels of the intrinsic defects in a series of halide double perovskites and to correlate them with the chemical potentials and experimental growth conditions. It was reported that Br vacancies are deep traps with a low formation energy under Br-poor conditions in Cs 2 AgBiBr 6 , , whereas another work indicated that Br vacancies create only a shallow defect level .…”
mentioning
confidence: 99%